Pengaruh Consumer Review dan Harga Produk terhadap Daya Saing pada Bisnis Online (Studi Kasus terhadap Pengguna Aplikasi Shopee di Kecamatan Campalagian, Kabupaten Polewali Mandar) - Ghazali, Rahmat; Nurmusdalifah, Nurmusdalifah; Sumarsih, Sumarsih; Qamariah, Nur (Universitas Sulawesi Barat, 2023)
This study aims to determine the effect of consumer reviews and product prices on competitiveness in online businesses (Case Study of Shopee Application Users in Campalagian District, Polewali Mandar Regency). This type of research is quantitative correlation and data collection techniques by distributing online and offline questionnaires. The sample used in this study was 66 respondents obtained by incidental sampling method. Data analysis methods, namely validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, multiple regression analysis test, t test (partial, F test (simultaneous), and multiple determination coefficient test using SPSS 20. The test results show that consumer reviews do not have a positive influence on the competitiveness of Shopee's online business in Campalagian District, on the contrary product prices have a positive and significant influence on business competitiveness on Shopee's online business in Campalagian District and consumer reviews and product prices together have a positive influence. on the competitiveness of Shopee's online business in Campalagian District.The product price variable greatly affects the competitiveness of Shopee's online business in Campalagian District.